Parenting Program to Protect Children's Privacy: The Phenomenon of Sharenting Children on social media - Robiatul Adawiah, Laila; Rachmawati, Yeni (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
Sharenting is a habit of using social media to share content that disseminates pictures, videos, information, and parenting styles for their children. The purpose of this article is to describe the sharenting phenomenon that occurs among young parents, and the importance of parenting programs, rather than protecting children's privacy. Writing articles use a qualitative approach as a literature review method that utilizes various scientific articles describing the sharenting phenomenon in various countries. The findings show that sharenting behaviour can create the spread of children's identity openly on social media and tends not to protect children's privacy and even seems to exploit children. Apart from that, sharenting can also create pressure on the children themselves and can even have an impact on online crime. This article is expected to provide benefits to parents regarding the importance of maintaining attitudes and behaviour when sharing and maintaining children's privacy and rights on social media. Keywords: Sharenting on social media, Children's Privacy, Parenting Program References: Åberg, E., & Huvila, J. (2019). Hip children, good mothers – children’s clothing as capital investment? Young Consumers, 20(3), 153–166. https://doi.org/10.1108/YC-06-2018-00816 Altafim, E. R. P., & Linhares, M. B. M. (2016). Universal violence and child maltreatment prevention programs for parents: A systematic review. Psychosocial Intervention, 25(1), 27–38. https://doi.org/10.1016/j.psi.2015.10.003 Archer, C., & Kao, K.-T. (2018). Mother, baby, and Facebook makes three: Does social media provide social support for new mothers? Media International Australia, 168(1), 122–139. https://doi.org/10.1177/1329878X18783016 Bartholomew, M. K., Schoppe-Sullivan, S. J., Glassman, M., Kamp Dush, C. M., & Sullivan, J. M. (2012). New Parents’ Facebook Use at the Transition to Parenthood. Family Relations, 61(3), 455–469. https://doi.org/10.1111/j.1741-3729.2012.00708.x Belk, R. W. (1988). Possessions and the Extended Self. Journal of Consumer Research, 15(2), 139. https://doi.org/10.1086/209154 Belk, R. W. (2013). Extended Self in a Digital World: Table 1. Journal of Consumer Research, 40(3), 477–500. https://doi.org/10.1086/671052 Benedetto, L., & Ingrassia, M. (2021). Digital Parenting: Raising and Protecting Children in Media World. In L. Benedetto & M. Ingrassia (Eds.), Parenting. IntechOpen. https://doi.org/10.5772/intechopen.92579 Berns, R. (2016). Child, family, school, community. Socialization and support. Stanford. United States of America, 5(64), 93–98. Bessant, C. (2017). Parental sharenting and the privacy of children. Northumbria University Faculty of Business and Law, Faculty and Doctoral Conference, 28th - 29th June 2017, Newcastle, UK. Bessant, C. (2018). Sharenting: Balancing the Conflicting Rights of Parents and Children. Communications Law, 23(1), 7–24. Bessant, C., & Nottingham, E. (2020). Sharenting in a socially distanced world. Parenting for a Digital Future., 1–2. Biglan, A., Flay, B. R., Embry, D. D., & Sandier, I. N. (2012). The Critical Role of Nurturing Environments for Promoting Human Weil-Being. American Psychologist, 16. Blum-Ross, A., & Livingstone, S. (2017). “Sharenting,” parent blogging, and the boundaries of the digital self. Popular Communication, 15(2), 110–125. https://doi.org/10.1080/15405702.2016.1223300 Brooks, J. (2008). The Process of Parenting. In The Process of Parenting (pp. 116–117). Pustaka Belajar. Brosch, A. (2016). When the child is born into the internet: Sharenting as a growing trend among parents on Facebook. New Educational Review, 43(1), 224–235. https://doi.org/10.15804/tner.2016.43.1.19 Brosch, A. (2018). Sharenting – Why do parents violate their children’s privacy? New Educational Review, 54(4), 75–85. https://doi.org/10.15804/tner.2018.54.4.06 Byrne, S., Rodrigo, M. J., & Máiquez, M. L. (2014). Patterns of individual change in a parenting program for child maltreatment and their relation to family and professional environments. Child Abuse & Neglect, 38(3), 457–467. https://doi.org/10.1016/j.chiabu.2013.12.008 Centers for Disease Control and Prevention. (2014). Understanding Child Maltreatment 2014 (p. 2). http://www.cdc.gov/violenceprevention/pdf/cm-factsheet-a.pdf Children’s Online Privacy Protection Act (COPPA). (2002). Protecting Children’s Privacy Under COPPA: A Survey on Compliance. Federal Trade Commission. http://www.ftc.gov/ogc/coppa1.htm Choi, G. Y., & Lewallen, J. (2018). “Say Instagram, Kids!”: Examining Sharenting and Children’s Digital Representations on Instagram. Howard Journal of Communications, 29(2), 144–164. https://doi.org/10.1080/10646175.2017.1327380 Collins English Dictionary. (2014). Opinion—Definition of opinion by The Free Dictionary. 12th Edition. http://dictionary.reference.com/browse/database Comer, J. S., & Barlow, D. H. (2014). The occasional case against broad dissemination and implementation: Retaining a role for specialty care in the delivery of psychological treatments. American Psychologist, 69(1), 1–18. https://doi.org/10.1037/a0033582 Durkin, K. F., & Bryant, C. D. (1999). Propagandizing pederasty: A thematic analysis of the on-line exculpatory accounts of unrepentant pedophiles. Deviant Behavior, 20(2), 103–127. https://doi.org/10.1080/016396299266524 Fitri, S. (2017). Dampak Foditif dan Negatif Sosial Media terhadap Sosial Anak. NATURALISTIC: Jurnal Kajian Penelitian Pendidikan Dan Pembelajaran, 1(2), 118–123. https://doi.org/10.35568/naturalistic.v1i2.5 Fox, A. K., & Hoy, M. G. (2019). Smart Devices, Smart Decisions? Implications of Parents’ Sharenting for Children’s Online Privacy: An Investigation of Mothers. Journal of Public Policy & Marketing, 38(4), 414–432. https://doi.org/10.1177/0743915619858290 Fridha, M., & Irawan, R. E. (2020). Eksploitasi Anak Melalui Akun Instagram (Analisis Wacana Kritis Praktek Sharenting oleh Selebgram Ashanty & Rachel Venya). Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 12(1), 68–80. https://doi.org/10.23917/komuniti.v12i1.10703 Friedman, S. J. (2000). Children and the World Wide Web. University Press of America. Hammond, S. I., Müller, U., Carpendale, J. I. M., Bibok, M. B., & Liebermann-Finestone, D. P. (2012). The effects of parental scaffolding on preschoolers’ executive function. Developmental Psychology, 48(1), 271–281. https://doi.org/10.1037/a0025519 Holzer, P. J., Higgins, J., Bromfield, L., Richardson, N., & Higgins, D. (2006). The effectiveness of parent education and home visiting child maltreatment prevention programs. Australian Institute of Family Studies. Koetse, M. (2019). ‘Sharenting’ on Chinese Social Media: When Parents Are Posting Too Many Baby Pics on WeChat. What’s on Weibo Reporting Social Trends in China. Krisnawati, E. (2016). Mempertanyakan Privasi di Era Selebgram: Masih Adakah? Jurnal IIlmu Komunikasi, 13(2), 179. https://doi.org/10.24002/jik.v13i2.682 Latipah, E., Adi Kistoro, H. C., Hasanah, F. F., & Putranta, H. (2020). Elaborating motive and psychological impact of sharenting in millennial parents. Universal Journal of Educational Research, 8(10), 4807–4817. https://doi.org/10.13189/ujer.2020.081052 Leaver, T. (2020). Balancing privacy: Sharenting, intimate surveillance, and the right to be forgotten. In The Routledge Companion to Digital Media and Children. https://doi.org/10.33767/osf.io/fwmr2 Lee, S. J., Ward, K. P., Chang, O. D., & Downing, K. M. (2021). Parenting activities and the transition to home-based education during the COVID-19 pandemic. Children and Youth Services Review, 122, 105585. https://doi.org/10.1016/j.childyouth.2020.105585 Lundahl, B., Risser, H., & Lovejoy, M. (2006). A meta-analysis of parent training: Moderators and follow-up effects. Clinical Psychology Review, 26(1), 86–104. https://doi.org/10.1016/j.cpr.2005.07.004 Lwin, M., Stanaland, A., & Miyazaki, A. (2008). Protecting children’s privacy online: How parental mediation strategies affect website safeguard effectiveness. Journal of Retailing, 84(2), 205–217. https://doi.org/10.1016/j.jretai.2008.04.004 Manganello, J. A., Falisi, A. L., Roberts, K. J., Smith, K. C., & McKenzie, L. B. (2016). Pediatric injury information seeking for mothers with young children: The role of health literacy and ehealth literacy. Journal of Communication in Healthcare, 9(3), 223–231. https://doi.org/10.1080/17538068.2016.1192757 Manotipya, P., & Ghazinour, K. (2020). Children’s Online Privacy from Parents’ Perspective. Procedia Computer Science, 177, 178–185. https://doi.org/10.1016/j.procs.2020.10.026 Marasli, M., Sühendan, E., Yilmazturk, N. H., & Cok, F. (2016). Parents’ shares on social networking sites about their children: Sharenting. Anthropologist, 24(2), 399–406. https://doi.org/10.1080/09720073.2016.11892031 Mikton, C., & Butchart, A. (2009). Child maltreatment prevention: A systematic review of reviews. Bulletin of the World Health Organization, 87(5), 353–361. https://doi.org/10.2471/BLT.08.057075 Miyazaki, A. D. (2008). Online Privacy and the Disclosure of Cookie Use: Effects on Consumer Trust and Anticipated Patronage. Journal of Public Policy & Marketing, 27(1), 19–33. https://doi.org/10.1509/jppm.27.1.19 Morris, A. S., Robinson, L. R., Hays-Grudo, J., Claussen, A. H., Hartwig, S. A., & Treat, A. E. (2017). Targeting Parenting in Early Childhood: A Public Health Approach to Improve Outcomes for Children Living in Poverty. Child Development, 88(2), 388–397. https://doi.org/10.1111/cdev.12743 Moser, C., Chen, T., & Schoenebeck, S. Y. (2017). Parents? And Children?s Preferences about Parents Sharing about Children on Social Media. Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems, 5221–5225. https://doi.org/10.1145/3025453.3025587 Nooraeni, R. (2017). Implementasi Program Parenting Dalam Menumbuhkan Perilaku Pengasuhan Positif Orang Tua Di PAUD Tulip Tarogong Kaler Garut. Jurnal Pendidikan Luar Sekolah, 13(2). Nottingham, E. (2013). ‘Dad! Cut that Part Out!’ Children’s Rights to Privacy in the Age of ‘Generation Tagged’: Sharenting, digital kidnapping and the child micro-celebrity. In Journal of Chemical Information and Modeling. O’Keeffe, G. S., Clarke-Pearson, K., & Council on Communications and Media. (2011). The Impact of Social Media on Children, Adolescents, and Families. PEDIATRICS, 127(4), 800–804. https://doi.org/10.1542/peds.2011-0054 Pan, X., & Yu, H. (2018). Different Effects of Cognitive Shifting and Intelligence on Creativity. The Journal of Creative Behavior, 52(3), 212–225. https://doi.org/10.1002/jocb.144 Prasetyo, Dimas., Syahnas, A. N. R., Fajriani, A., Nugraha, H. G., & Suryani, S. (2019). “Saya hanya mengunggah foto dan video anak saya ”. Intenational Conference on ECEP. Putra, A. M., & Febrina, A. (2019). Fenomena Selebgram Anak: Memahami Motif Orang tua. Jurnal ASPIKOM, 3(6), 1093–1108. https://doi.org/10.24329/aspikom.v3i6.396 Sakashita, M., & Kimura, J. (2011). Daughter as Mother’s Extended Self. In European advances in consumer research (In A. Bradshaw, C. Hackley, P. Maclaran (Eds.), Vol. 9, pp. 283–289). Association for Consumer Research. Salleh, A. S., & Noor, N. A. Mohd. (2019). Sharenting: Implikasinya dari Persepektif Perundangan Malaysia. Jurnal Undangundang Malaysia, 31(1), 121–156. Sanders, M. (2012). Development, evaluation, and multinational dissemination of the triple P-Positive Parenting Program. Annual Review of Clinical Psychology, 8, 345–379. Santini, P. M., & Williams, L. C. (2016). Parenting Programs to Prevent Corporal Punishment: A Systematic Review. Paidéia (Ribeirão Preto), 26(63), 121–129. https://doi.org/10.1590/1982-43272663201614 Sarkadi, A., Dahlberg, A., Fängström, K., & Warner, G. (2020). Children want parents to ask for permission before ‘sharenting’. Journal of Paediatrics and Child Health, 56(6), 981–983. https://doi.org/10.1111/jpc.14945 Shumaker, C., Loranger, D., & Dorie, A. (2017). Dressing for the Internet: A study of female self-presentation via dress on Instagram. Fashion, Style & Popular Culture, 4(3), 365–382. https://doi.org/10.1386/fspc.4.3.365_1 Siibak, A., & Traks, K. (2019). Viewpoints The dark sides of sharenting. Catalan Journal of Communication & Cultural Studies, 11(1), 115–121. https://doi.org/10.1386/cjcs.11.1.115 Sobur, A. (2001). Pers, Hak Privasi, dan Hak Publik. Mediator, 2(1), 81–91. http://dx.doi.org/10.24329/aspikom.v3i6.396 Steinberg, S. B. (2017). Sharenting: Children’s Privacy in the Age of social media. EMORY LAW JOURNAL, 66, 47. Traube, D. E., Hsiao, H.-Y., Rau, A., Hunt-O’Brien, D., Lu, L., & Islam, N. (2020). Advancing Home Based Parenting Programs through the Use of Telehealth Technology. Journal of Child and Family Studies, 29(1), 44–53. https://doi.org/10.1007/s10826-019-01458-w Trivette, C. M., & Dunst, C. J. (2009). Community-Based Parent Support Programs. 7. van der Velden, M., & El Emam, K. (2013). “Not all my friends need to know”: A qualitative study of teenage patients, privacy, and social media. Journal of the American Medical Informatics Association, 20(1), 16–24. https://doi.org/10.1136/amiajnl-2012-000949 Verswijvel, K., Walrave, M., Hardies, K., & Heirman, W. (2019). Sharenting, is it a good or a bad thing? Understanding how adolescents think and feel about sharenting on social network sites. Children and Youth Services Review, 104, 104401. https://doi.org/10.1016/j.childyouth.2019.104401 Wagner, A., & Gasche, L. A. (2018). Sharenting: Making decisions about other’s privacy on social networking sites. MKWI 2018 - Multikonferenz Wirtschaftsinformatik. World Health Organization (WHO). (2016). INSPIRE seven strategies for ending violence against children. World Health Organization. Wyatt Kaminski, J., Valle, L. A., Filene, J. H., & Boyle, C. L. (2008). A Meta-analytic Review of Components Associated with Parent Training Program Effectiveness. Journal of Abnormal Child Psychology, 36(4), 567–589. https://doi.org/10.1007/s10802-007-9201-9 Zeeuw, A. De, Media, M. A. N., & Culture, D. (2018). Exposing Childhoods Online (Issue June).